NABYWANIE AKCJI WŁASNYCH W CELU UMORZENIA - Sójka, Tomasz (Wydział Prawa i Administracji UAM, 2002)
Repurchase of shares for the purpose of their redemption is one of the exemptions to the general rule that forbids companies to buy their own shares back. Thus, the Polish code of commercial partnerships and companies sets out a series of restrictions for the re-acquisition of shares for the purpose of their redemption. These limitations aim at protecting the creditors and minority shareholders of a given company. If the buy-back is financed with distributable profits of the company, the precondition for the repurchase of shares is to devote the profits to this end. If the company has no distributable profits, the repurchase must follow the decision of the general meeting to reduce the legal capital. The conditions for the share buy-back are infringed by the company’s duty to return the shares to the seller. On the other hand, the shareholder who sold the shares is obliged to pay-back the price. A company repurchasing its own shares ought to comply with the rule of equal treatment of shareholders. According to the rule any unequal treatment o f shareholders is only allowed if it is clearly in the interest o f the company as a whole. After the repurchase of shares a company does not have to obtain a permission from the former shareholders to redeem them. It is assumed that a shareholder permits their redemption by selling his shares to the company.
REPURCHASE OF SHARES FOR THE PURPOSE OF THEIR REDEMPTION